2006
DOI: 10.1007/s00464-004-2181-8
|View full text |Cite
|
Sign up to set email alerts
|

Complications in laparoscopic myomectomy

Abstract: Morbidity was low. Age had no impact. Laparoscopic myomectomy can be offered to all women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
1
29
0
8
Order By: Relevance
“….Vavilis et al reported that the incidence of pyrexia in first 48 hours was 16.1 % in the abdominal myomectomy group. 13 The intraoperative complication rate was (3.22%). Altqassen et al noted an intraoperative complication rate of 2.6%.…”
Section: Methodsmentioning
confidence: 95%
“….Vavilis et al reported that the incidence of pyrexia in first 48 hours was 16.1 % in the abdominal myomectomy group. 13 The intraoperative complication rate was (3.22%). Altqassen et al noted an intraoperative complication rate of 2.6%.…”
Section: Methodsmentioning
confidence: 95%
“…Ello se hace más evidente cuando se compara pacientes operadas por mioma menor de 5 cm. Cabe señalar, que nuestros resultados por laparoscopia son comparables a series internacionales en cuanto a tiempo quirúrgico y tasa de complicaciones (14,(16)(17)(18). Recientemente se publicó un estudio randomizado multicéntrico comparando la miomectomía laparoscópica con la realizada por minilaparotomía, que demostró beneficios a favor de la minilaparotomía en términos del tiempo de enucleación del mioma y número de histerotomías.…”
Section: Discussionunclassified
“…Laparoscopic myomectomy minimizes the size of the abdominal incision, resulting in a quicker postoperative recovery, a shorter time to hospital discharge, reduced analgesic requirements and less blood loss. Because of the complex nature of laparoscopic dissection and suturing, special surgical expertise typically is required (Altgassen et al, 2006;Sizzi et al, 2007). Robot-assisted laparoscopic surgery also has been used to perform myomectomy.…”
Section: Myomectomymentioning
confidence: 99%